Massive Open Online Course (MOOC), Widyaiswara and Competency Development for Civil Servants - Ratnaningsih Hidayati; Nadya Megawati Rachman (Perwakilan BKKBN Daerah Istimewa Yogyakarta, 2021)
The outbreak of the Covid 19 pandemic accelerated distance learning. Face-to-face learning activities in Civil servant or Aparatur Sipil Negara (ASN) training are replaced by e-learning, and this is a significant transformation. The purpose of this study was to investigate the extent to which the learning facilitators or Widyaiswara were prepared for ASN learning in facing the shift of the learning model from conventional face-to-face to e-learning. This research used a qualitative approach. The data mining technique employed was interviews with ten young, middle, and senior Widyaiswara. The author also carried out data from secondary sources in discussions in the Widyaiswara Community and information sharing activities, and other related library sources. The results indicated most of Widyaiswara were ready to face the change of the learning paradigm. However, Widyaiswara needs to develop digital literacy skills, such as the use of information technology for learning and creating an e-learning program/learning materials that meet the needs of training participants. The Widyaiswara Advisory Body, namely the National Institute of Public Administration Indonesia (NIPA-LAN), is expected to provide guidance to Widyaiswara and enable government training institutions to prepare their Widyaiswara to be ready and professional use of learning technology.